Durable Responses and Low Toxicity After Fast Off-Rate CD19 Chimeric Antigen Receptor-T Therapy in Adults With Relapsed or Refractory B-Cell Acute Lymphoblastic Leukemia. Issue 30 (20th October 2021) - Roddie, Claire; Dias, Juliana; O'Reilly, Maeve A.; Abbasian, Mahnaz; Cadinanos-Garai, Amaia; Vispute, Ketki; Bosshard-Carter, Leticia; Mitsikakou, Marina; Mehra, Vedika; Roddy, Harriet; Hartley, John A.; Spanswick, Victoria; et al.
Abstract : PURPOSE: Prognosis for adult B-cell acute lymphoblastic leukemia (B-ALL) is poor, and there are currently no licensed CD19 chimeric antigen receptor (CAR) therapeutics. We developed a novel second-generation CD19-CAR (CAT19-41BB-Z) with a fast off rate, designed for more physiologic T-cell activation to reduce toxicity and improve engraftment. We describe the multicenter phase I ALLCAR19 (NCT02935257 ) study of autologous CAT19-41BB-Z CAR T cells (AUTO1) in relapsed or refractory (r/r) adult B-ALL. METHODS: Patients age ≥ 16 years with r/r B-ALL were eligible. Primary outcomes were toxicity and manufacturing feasibility. Secondary outcomes were depth of response at 1 and 3 months, persistence of CAR-T, incidence and duration of hypogammaglobulinemia and B-cell aplasia, and event-free survival and overall survival at 1 and 2 years. RESULTS: Twenty-five patients were leukapheresed, 24 products were manufactured, and 20 patients were infused with AUTO1. The median age was 41.5 years; 25% had prior blinatumomab, 50% prior inotuzumab ozogamicin, and 65% prior allogeneic stem-cell transplantation. At the time of preconditioning, 45% had ≥ 50% bone marrow blasts. No patients experienced ≥ grade 3 cytokine release syndrome; 3 of 20 (15%) experienced grade 3 neurotoxicity that resolved to ≤ grade 1 within 72 hours with steroids. Seventeen of 20 (85%) achieved minimal residual disease–negative complete response at month 1, and 3 of 17 underwent allogeneic stem-cell transplantation while in remission. The event-free survival at 6 and 12 months was 68.3% (42.4%-84.4%) and 48.3% (23.1%-69.7%), respectively. High-level expansion (Cmax 127, 152 copies/µg genomic DNA) and durable CAR-T persistence were observed with B-cell aplasia ongoing in 15 of 20 patients at last follow-up. CONCLUSION: AUTO1 demonstrates a tolerable safety profile, high remission rates, and excellent persistence in r/r adult B-ALL. Preliminary data support further development of AUTO1 as a stand-alone treatment for r/r adult B-ALL. Abstract :